A taxonomic revision of Solenostomataceae (Marchantiophyta) in Korea - BAKALIN, Vadim V; CHOI, Seung Se; PARK, Seung Jin; SIM, Sun Hee; HYUN, Chang Woo (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2020)
Solenostomataceae are revised for the Korean Peninsula. In total, 27 species in four genera (Metasolenostoma, Plectocolea, Protosolenostoma, Solenostoma) are recorded, the occurrence of 24 of which is confirmed. Each confirmed species is provided with an ecological overview, and a list of specimens examined and illustrations based on materials from Korea. Solenostoma jirisanense sp. nov. is described.